THE EVER-CHANGING DYNAMIC OF CONFLICTS IN GEORGIA: THE INTERPLAY BETWEEN INTERNAL AND EXTERNAL FACTORS - SHAFEE, Fareed (CENTRAL ASIA AND THE CAUCASUS, 2015)
In this article, I will trace the dynamics and changes in internal conflicts in Georgia (Georgian-Ossetian and Georgian Abkhazian conflicts) and investigate the role of external factors and their interplay with internal factors affecting the dynamic of the conflicts. Mainstream academic literature views the two conflicts as internal. However, after the war in August 2008 that saw visible intervention from Russia, the conflicts, I argue, have turned into intra-state conflict between Georgia and Russia. My further argument is about the decisive role of external factors in the conflicts. The Western and Georgian media tend to emphasize the role of Russia in the conflicts; academic literature is divided over the issue of the influence of external factors. I acknowledge that sometimes Russia’s role is exaggerated, and that less attention is paid, particularly in Georgia, to Tbilisi’s wrongdoings. However, overall, the presence and influence of external factors, on at least two occasions, modified the dynamic of the conflicts. Here, along with Russia, other outside players, such as the United States, contributed to the conflicts.